2008
DOI: 10.3801/iafss.fss.9-155
|View full text |Cite
|
Sign up to set email alerts
|

Study of Radiant Smoldering Ignition of Plywood Subjected to Prolonged Heating Using the Cone Calorimeter, TGA, and DSC

Abstract: Maple plywood samples were heated in an oven at 180°C to a residual weight of 70%, 50%, and 30% of the virgin weight. The virgin plywood and the thermally pretreated samples were tested in a cone calorimeter over the range of 6 to 15 kW/m 2 without the use of an ignitor. Tests were conducted until smoldering/glowing combustion was observed or for eight hours if ignition was not observed. The extent of thermal pretreatment of the plywood had no measurable effect on the minimum heat flux for smoldering ignition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Under radiant heat fluxes, the ignition temperature is significantly affected by the moisture content [49]. Earlier studies [35,41,46,49,109,110] have shown that the samples containing moisture have increased ignition temperature and reduced smoldering velocity. Kuznetsov and Filkov [46] quantified the effect of moisture content on the ignition of various wood species and reported that an increase in moisture content in wood by a factor of 10 resulted in increasing its ignition time by more than 50 %.…”
Section: Fuel Moisture Contentmentioning
confidence: 99%
See 4 more Smart Citations
“…Under radiant heat fluxes, the ignition temperature is significantly affected by the moisture content [49]. Earlier studies [35,41,46,49,109,110] have shown that the samples containing moisture have increased ignition temperature and reduced smoldering velocity. Kuznetsov and Filkov [46] quantified the effect of moisture content on the ignition of various wood species and reported that an increase in moisture content in wood by a factor of 10 resulted in increasing its ignition time by more than 50 %.…”
Section: Fuel Moisture Contentmentioning
confidence: 99%
“…This process absorbs heat which, in a dry sample, would otherwise pyrolyze the fuel. Swann et al [41] studied the effect of preheating on the smoldering ignition of maple plywood. They concluded that the preheating of the wood had little effect on the minimum heat flux for ignition and the ignition temperature; however, the time to ignition was markedly reduced by the prolonged preheating that essentially removed moisture from the plywood.…”
Section: Fuel Moisture Contentmentioning
confidence: 99%
See 3 more Smart Citations